A dual‐band dual‐polarized end‐loaded quasi‐open‐sleeve dipole antenna with stable pattern for wireless local area network applications. Issue 3 (17th January 2019) - Sun, Li; Sun, Baohua; Zhang, Guanxi; Zhao, Jianping
Abstract: This article presents a dual‐band dual‐polarized end‐loaded quasi‐open‐sleeve dipole antenna (ELQOSDA) with stable radiation patterns for WLAN applications. The ELQOSDA consists of an end‐loaded planar dipole and two parasitic strips. Dual polarization is obtained by two ELQOSDAs perpendicularly crossing, with some parts overlapped. The unidirectional stable radiation patterns are achieved by adding a square resonance ring between the ground plane and antenna. The ring has little influence on antenna performance at the lower frequency, but improves the coupling currents between the ground and antenna at the upper frequency. As a result, satisfactory dual band and broadside radiation performance is obtained. For demonstration, the proposed antenna is implemented. Measured dual‐band 10‐dB impedance bandwidths are 9.4% (2.33‐2.56 GHz) and 33.5% (4.23‐5.93 GHz) in the lower and upper bands, covering the entire WLAN 2.4/5.2/5.8‐GHz bands. Moreover, the measured antenna has a 6.7‐8.1 dBi broadside gain and stable radiation patterns over the whole operating band.